La idiosincrasia del lenguaje almodovariano y su repercusión sobre la traducción. Analisis de algunas de las soluciones en el campo de la variación lingüística del subtitulado en polaco de “Volver” (2006) - Ciordia, Leticia Santamaría (Studia Romanica Posnaniensia, 2012)
The identification of an original and idiosyncratic style in the work of the Spanish filmmaker Pedro Almodóvar provides the tone of the speech with a semantic function: linguistic variation and specific registers help to transmit the message and intention of the author. As a consequence of this, the possibilities for the translation being carried away in similar linguistic terms to those of the original text will be higher than in texts without linguistic peculiarities or stylistically unmarked. The purpose of this paper is to reflect on the influence exerted by the original author in the reception of his work abroad and, consequently, in its translation. In this sense, we will analyse the informative value of certain linguistic uses as well as the importance of enriching stylistically the subtitles in these connotative texts through the example of Almodóvar’s film "Volver" and its translation into Polish (2006).